Allometric relationships of six fish species of the order Characiformes in oxbow lakes on the floodplain of the middle Purus river, Amazon - Pereira Oliveira, Lucas (2022)
The length-weight relationship (LWR) was estimated for six fish species of the order Characiformes: Curimatella meyeri, Hoplias malabaricus, Potamorhina altamazonica, Potamorhina latior, Pygocentrus nattereri, Schizodon fasciatus, collected from oxbow lakes on the floodplain of the middle Purus River in western Brazilian Amazonia. The specimens were collected in January, May, and September 2012, during both diurnal and nocturnal periods. Allometric coefficients (b) for the studied species ranged between 2.98 and 3.34. The correlation coefficients for the LWR (r2) ranged between 0.954 and 0.993. The data presented here provide important insights for the development of effective measures for the conservation and management of the study species.